Performance and Effort Expectancy on Behavioral Intentions and Their Implications for Fintech Use Behavior in Indonesia - Hendra Hadiwijaya; Muhammad Fajar Ariwibowo (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
This research aims to determine the influence of Performance and Effort Expectancy on Behavioral Intentions and the implications for fintech Use behavior. The population in this research are people in Indonesia who have used Fintech. Purposive sampling was used in this research. The sample taken was 280 respondents. The analysis technique used in this research is structural equation modeling (SEM). The research results show that Performance and Effort Expectancy positively affect Fintech Behavioral Intentions in Indonesia. Performance, effort, Expectations, and Behavioral Intentions positively influence Fintech Use behavior. Behavioral Intentions have a greater influence on Fintech Use behavior in Indonesia than Performance expectancy and Effort Expectancy on Fintech in Indonesia. Performance and Effort Expectancy positively influence Behavioral Intentions and their Implications for Fintech Use behavior in Indonesia. Effort Expectancy has a greater influence than Performance expectancy on Behavioral Intentions, and its Implications for Fintech Use behavior in Indonesia.